OFR-145-77 Improvements For Mine Carrier Phone Systems - Richard H. Spencer (The National Institute for Occupational Safety and Health (NIOSH), 1977)
The purpose of this program was threefold: (1) to identify the symptoms of poor or inadequate performance of trolley carrier phone systems; (2) to assess the root causes of performance difficulties and classify them on the basis of equipment, coupling, or transmission; (3) to propose, analyze, test, evaluate and verify means of overcoming performance difficulties. Based on interviews and discussions with knowledgeable persons, laboratory experiments, and in-mine measurements, it was determined that the major impediment to good carrier phone system performance is the extreme signal attenuation found on the trolley wire/rail largely due to the many bridging loads. Three means are identified to help overcome the performance difficulties: the low impedance trolley wire, a method of improving performance by capacitively loading the transmission line; the dedicated wire, a low-loss means of extending trolley signal coverage; the use of isolators to remove the offending bridging loads at the carrier frequency. Other subjects treated in the report are design reviews of hardware, guidelines for the use of information in the report, recommendations, and a description of a probe for measuring trolley wire current.